(untitled) (Global Journal of Science Frontier Research, 2020)
To treat the cause of a disease and not only its effects is of the utmost importance; hence, we need to know the origin of this pandemic of COVID-19, in order to be able, if possible, to prevent an event of such a nature and magnitude in the future, and to be able to avoid every sort of abuses to humanity, as it is happening right now. Bullet points here addressed are: 1) To have, inside the backbone of a virus from a bat (mostly 97.55% of the viral RNA (by deducting the HIV inserts found by Perez, Montagnier and others), & as per the findings of Petrovsky, see below, and also to contrast the differences), the insertion similar to that of a pangolin virus for the Receptor Binding Domain (RBD, which basically consists of six separated key amino acids, or the 0.06% of its genome for these particular 18 nucleotides), being their receptor the ACE2 of the human lung, appearing at a time (as earlier as since September of 2019), were there were already mature all of the molecular methodologies necessary to modify individual nucleotides (Crispr-Cas9, "Seamless", etc.) that then modify at will the resulting amino acids, with the possibility to give an extra passage to the virus through ferrets (or other lab animals) that have an ACE2 very similar to the humans, to give it then a more "natural" appearance (by random trivial changes); because, had it been natural.